1998
DOI: 10.1136/bmj.316.7135.899
|View full text |Cite
|
Sign up to set email alerts
|

Mental health problems of homeless children and families: longitudinal study

Abstract: Objective: To establish the mental health needs of homeless children and families before and after rehousing. Design: Cross sectional, longitudinal study. Setting: City of Birmingham. Subjects: 58 rehoused families with 103 children aged 2-16 years and 21 comparison families of low socioeconomic status in stable housing, with 54 children. Main outcome measures: Children's mental health problems and level of communication; mothers' mental health problems and social support one year after rehousing. Results: Men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
59
0
2

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(69 citation statements)
references
References 7 publications
8
59
0
2
Order By: Relevance
“…Previous research regarding the characteristics of homeless families has found a history of adversity (e.g. Bassuk et al, 1997;Bassuk et al, 2001), mental health problems among mothers and children (Vostanis et al, 1998;Anooshian, 2005), and limited access to services (Cumella et al, 1998). Very little attention has been given to the experiences of families following their exit from homelessness.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research regarding the characteristics of homeless families has found a history of adversity (e.g. Bassuk et al, 1997;Bassuk et al, 2001), mental health problems among mothers and children (Vostanis et al, 1998;Anooshian, 2005), and limited access to services (Cumella et al, 1998). Very little attention has been given to the experiences of families following their exit from homelessness.…”
Section: Introductionmentioning
confidence: 99%
“…The current study focuses on psychosocial issues related to homelessness and resettlement as much previous UK research in this field has concentrated on structural issues such as housing policy (Christian, 2003). Vostanis et al, 1998). The majority of these women conform to Schein's (1982) 'ABC' factors which characterise economically poor single mothers.…”
Section: Introductionmentioning
confidence: 99%
“…These levels of mental ill health have been found significantly higher than matched socioeconomically deprived but housed groups (i.e. living in stability- Connelly & Crown, 1994;Conway, 1988;Vostanis, Grattan, & Cumella 1998;Zima, Wells, Benjamin, & Duan 1996). Toro et al (1995) suggested that psychopathology was both cause and effect of homelessness.…”
Section: Homelessness As An Outcome Of Multiple Adversities and Traummentioning
confidence: 94%
“…This community sector of care provides an ideal setting in which to embed evidence-based prevention services into an existing service structure. Children who live in supportive housing are at high risk for serious mental health problems and are in need of a continuum of mental health services (Vostanis, Grattan, & Cumella, 1998). Moreover, single-site supportive housing affords a rather unique opportunity to engage families in prevention programming as caregivers and children have easy access to program activities that are delivered in their housing units.…”
Section: Community Sectors-of-carementioning
confidence: 99%